Sequence variation in PPP1R13L results in a novel form of cardio‐cutaneous syndrome. Issue 9 (September 2017) - Falik‐Zaccai, Tzipora C; Barsheshet, Yiftah; Mandel, Hanna; Segev, Meital; Lorber, Avraham; Gelberg, Shachaf; Kalfon, Limor; Ben Haroush, Shani; Shalata, Adel; Gelernter‐Yaniv, Liat; Chaim, Sarah; Raviv Shay, Dorith; et al.
Abstract :